On the shoulder of giants: advice for beginning teacher educators. Issue 5 (20th October 2021) - White, Simone; Murray, Jean; Goodwin, A. Lin; Kosnik, Clare; Beck, Clive
ABSTRACT: Teacher educators are an occupational group who appear to suffer from an identity crisis. They do not seem to be able to agree on what their role or professional learning needs are. This situation has dire consequences for the next generation of teacher educators who enter the field in the same rather haphazard and ad hoc way as the ones before. This phenomenon might further explain why it has been called the hidden profession with reports of a general lack of professional induction, mentoring and advice. To explore this issue, a study of twenty "accomplished" university-based teacher educators were posed questions, one in particular asked, "what advice would you give beginning teacher educators" ? A key finding is the important role a teacher educator plays as a public intellectual and the new skills and knowledges required to fulfil this role in an increasingly complex, multifaceted and digital world. 33